Prognostic Value of the Cumulative Cisplatin Dose During Concurrent Chemoradiotherapy in Locoregionally Advanced Nasopharyngeal Carcinoma: A Secondary Analysis of a Prospective Phase III Clinical Trial. (5th August 2016) - Peng, Hao; Chen, Lei; Zhang, Yuan; Li, Wen-Fei; Mao, Yan-Ping; Zhang, Fan; Guo, Rui; Liu, Li-Zhi; Lin, Ai-Hua; Sun, Ying; Ma, Jun
Abstract : Background: The objective of this study was to evaluate the prognostic value of the cumulative cisplatin dose (CCD) for long-term survival outcomes after concurrent chemoradiotherapy (CCRT) in locoregionally advanced nasopharyngeal carcinoma (NPC). Methods: Patients were included in an open-label phase III multicenter randomized controlled trial performed at seven institutions in China, and the 298 patients receiving CCRT only were assessed. Patient survival between different CCD groups were compared. Results: Median CCD for the 298 patients was 240 mg/m 2 (range, 40–320 mg/m 2 ); 113 (37.9%) patients received a CCD of <240 (≤200) mg/m 2, and 185 (62.1%) received a CCD of ≥240 mg/m 2 . For CCD of ≥240 mg/m 2 vs. <240 mg/m 2, the estimated 5-year overall survival, disease-free survival, locoregional relapse-free survival, and distant metastasis-free survival rates were 83.2% vs. 76.2% ( p = .403), 73.5% vs. 67.8% ( p = .461), 90.4% vs. 86.8% ( p = .551), and 82.6% vs. 79.7% ( p = .632), respectively. Multivariate analysis demonstrated that CCD (240 mg/m 2 ) was not an independent prognostic factor in either the entire cohort or stage III/IV subgroup. Conclusion: A CCD of ≥240 mg/m 2 was not an independent prognostic factor in patients with locoregionally advanced NPC at high risk of distant metastasis, and 200 mg/m 2 cisplatin may be adequate to achieve a survival benefit. Abstract : This study evaluated the prognostic value of the cumulative cisplatin dose (CCD) for long-term survival outcomes after concurrent chemoradiotherapy in locoregionally advanced nasopharyngeal carcinoma (NPC). A CCD of ≥240 mg/m 2 was not an independent prognostic factor in patients with locoregionally advanced NPC at high risk of distant metastasis, and 200 mg/m 2 cisplatin may be adequate to achieve a survival benefit.